X-Men - Bergen, Lara. (New York : Dell Yearling, 2000)
"Professor X. Jean Grey. Cyclops. Storm. Wolverine. Rogue. They are the X-Men, and together they must save the human race--and themselves--from destruction" -- Back cover.
"A major motion picture from Twentieth Century Fox" -- Front cover.
Keywords: X-Men (Fictitious characters) -- Fiction; Heroes -- Fiction; Adventure and adventurers -- Fiction; Adventure stories; Science fiction; Fantasy fiction